The Political Economy of Corruption and and the Role of Financial Institutions - Christa Hainz; Kira Boerner (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
In transition and developing countries, we observe rather high levels of corruption even they have democratic political systems. This is surprising from a political economy perspective, as a majority of the people generally suffers from high corruption levels. Our model based on the fact that corrupt officials have to pay an entry fee to get lucrative positions. In a probabilistic voting model, we show that a lack of financial institutions can lead more corruption as more voters are part of the corrupt system. Well-functioning financial institutions, in turn, can increase the political support for anti-corruption measures.
Keywords: D72; O17; D73; 330; Corruption; Financial Markets; Institutions; Development; Voting